Prognostic impact of rheumatic diseases in patients with heart failure with mildly reduced ejection fraction - Görtz, Michelle; Schupp, Tobias; Dudda, Jonas; Weidner, Kathrin; Lau, Felix; Schmitt, Alexander; Abel, Noah; Abumayyaleh, Mohammad S. A.; Steffen, Henning Johann; Langer, Harald; Dürschmied, Daniel; Akın, Ibrahim; et al. (Clinical research in cardiology, 2025)
Background Emerging evidence suggests that inflammatory conditions and comorbidities have a prognostic impact on patients with heart failure with mildly reduced ejection fraction (HFmrEF) in particular. This study aims to investigate the influence of rheumatic comorbidities on clinical outcomes in HFmrEF patients. Methods This retrospective cohort study included patients hospitalized with HFmrEF at a tertiary care center in Germany between January 2016 and December 2022. Patients hospitalized with HFmrEF were divided in two groups - with and without rheumatic diseases - and were compared with regard to the primary endpoint all-cause mortality at 30 months, as well as the key secondary endpoint HF-related rehospitalization. Results From a total of 2,184 patients with HFmrEF, 47 (2.2%) were diagnosed with a rheumatic disease. There was no significant difference in distribution of age (median 75 years vs. 76 years, p = 0.532), sex (males: 55.3% vs. 64.8%; p = 0.181) and cardiovascular comorbidities between patients with and without rheumatic diseases. The presence of rheumatic disease was not associated with the risk of all-cause mortality at 30 months (HR = 0.765; 95% CI 0.432-1.354; p = 0.358). However, patients with rheumatic diseases were associated with a higher risk of rehospitalization for HF at 30 months (HR = 2.088; 95% CI 1.171-3.723; p = 0.013). This association was still observed after multivariable adjustment (HR = 2.360; p = 0.006). Conclusion Patients with HFmrEF and coexisting rheumatic diseases did not exhibit increased 30-month all-cause mortality. However, the risk of rehospitalization was significantly higher in patients with rheumatic diseases. Graphical Abstract